2022
DOI: 10.7759/cureus.24639
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Prompt Management of Morel-Lavallée Lesions

Abstract: The Morel-Lavallée lesion (MLL) is a closed soft-tissue injury that is frequently associated with high-intensity trauma. The thigh, hip, and pelvic regions are the most typically affected regions. It is critical to recognize and treat an MLL as soon as possible because it is often neglected or its identification is delayed because of other distracting injuries in a polytrauma patient. Bacterial colonization of these closed soft-tissue wounds can result in an increased risk of perioperative and postoperative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…Previous reports have shown that the infection rate increases over time even when the wound is closed [ 1 , 2 ]. Early intervention is therefore advisable [ 4 ]. However, there are currently no reports on the use of various treatment modalities, including observation, puncture aspiration, surgical drainage, drain placement, open surgical lavage, or negative pressure closure [ 2 , 4 - 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the infection rate increases over time even when the wound is closed [ 1 , 2 ]. Early intervention is therefore advisable [ 4 ]. However, there are currently no reports on the use of various treatment modalities, including observation, puncture aspiration, surgical drainage, drain placement, open surgical lavage, or negative pressure closure [ 2 , 4 - 6 ].…”
Section: Discussionmentioning
confidence: 99%